Improvement on Distinguishing ‘B’ and ‘D’ Letter : Direct Instruction Flashcards Intervention for A Slow Learner - Anjani, Siti Dwita; Kurniawati, Farida (Universitas Pendidikan Mandalika, 2025)
This research aimed to evaluate the effectiveness of Direct Instruction (DI) Flashcards in helping a slow learner distinguish between the letters ‘b’ and ‘d’ using a pretest-posttest experimental design with an A-B structure. Data was gathered through observations and IQ testing. Through IQ testing, the subject ‘s intelligence capacity score fell in the Borderline Intellectual Functioning category (IQ = 83, Wechsler scale). Observations showed that the subject was a quiet student at school and rarely interacted with peers due to low self-esteem. Direct Instruction (DI) Flashcards are effective for students with poor cognitive capacity and low self-esteem due to their structured approach. This method provides clear expectations, explicit instruction, and consistent feedback, fostering a sense of competence and confidence in slow learners. The subject underwent a series of five sessions, including a pre-test, practice activities, and a post-test. Pretest and posttest scores were recorded, noting the number of correct and incorrect words to assess reading improvement. Observations during treatment sessions provided qualitative insights into the subject's learning process, highlighting specific challenges and strategies that enhanced performance. Error patterns were identified and addressed to improve reading accuracy. The findings of this research confirm that using direct instruction flashcards as a reading practice method is effective to improve slow learner student’s reading skills. This research underscores the value of tailored interventions for students with learning difficulties, such as slow learners. Effective interventions rely on attentive observation from teachers or caregivers to understand the challenges faced by the student, timely feedback to enhance self-awareness, and consistent encouragement to boost motivation and engagement in practice.